(3MGTjI ejQRG eMeO OjdeGL Ydi TQM GddeYIs - (3eMeO OjdeGLs
(3ChdgG (B:s
(3fYe dh RGd GdJZjjQ jfRM GdOdh GdChd Cecf GdGLJRGA HeG Hbj ef GdYOO MJi jceds
(3BNQgG (B:s
(3GdbOeGA GJHYhG YHGQGJ GdCMGOjK aj GdMce hLQJ Ydjge YGOJge adG NdGa aj GdJbQjX EdG aj GdYHGOI(B... (3Je gPG GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis